Traumatic injuries on the crania from the Novo-Sasykul cemetery - V.V. Kufterin; S.L. Vorobyeva (Вестник археологии, антропологии и этнографии, 2020)
This study is focused on the cranial sample from the Novo-Sasykul cemetery of the Pyany Bor Culture in the Lower Kama region (Bakaly District, Republic of Bashkortostan). The Novo-Sasykul cemetery is dated to the 1st–2nd c. AD, and it is fully excavated. The frequency of traumatic injuries has been analyzed in a sample consisting of 94 skulls of adult individuals (47 males, 47 females) stored in the Bashkortostan National Museum (Ufa). Injuries have been examined according to recommendations and methods used in the forensic medicine and paleopathology. The distribution of traumas was studied depending on sex and the side of the skull (left / right or frontal / dorsal). The intergroup variability of the ratios of combat traumas was studied with the involvement of a number of the Early Iron Age samples. The differences in frequencies were analyzed using the chi-squared test and two-tailed Fisher's exact test. It has been noted that the analysed sample is characterized by the high level of fatal combat injuries. In total, 16 injuries were recorded on 12 skulls (21.3 % in males, 4.3 % in females). A significantly larger number of traumas are localized on the left side of the skull, which may indicate a predominant strike direction from right to left. The identified traumatic injuries are grouped into five types. With the exception of one case of injury by a trilobate bone arrowhead, all injuries are qualified as blade weapon traumas. All traumas are perimortal, without any traces of healing. Against a comparative background, the studied sample is characterized by the high level of combat traumas, similar to those of the Late Sarmatian population from Esaulovskiy Aksai, the Hun from Ulangom, and the Bulan-Koba Culture sample from the Stepushka cemetery. However, archaeologically identified low level of armament of the Novo-Sasykul cemetery population, as well as the short period of the cemetery functioning, testify against the regular involvement of the analyzed group in armed conflicts. The high frequency of combat cranial traumas in this group, considering its low militarization, represented mainly by iron and bone arrowheads with a small amount of melee weapons, suggests that the Pyany Bor groups were more likely to be subjected to armed raids, acting more often as victims. Taking into account the planigraphy of the burials from which the injured skulls originate, it has been concluded that this part of the studied group died as a result of a possibly single armed conflict.